2021
DOI: 10.1017/pds.2021.111
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Shaped Seat-Pan Cushion to Improve Postural (Dis)comfort Reducing Pressure Distribution and Increasing Contact Area at the Interface

Abstract: Remaining seated for extended periods increases the risk health issues and discomfort perception. Consequently, the seat-pan design is crucial and could be mainly influenced by two factors: pressure distribution and seat contour. For seat pan discomfort, the lower average pressure is accompanied by less discomfort. Moreover, a seat contour with a large contact area is correlated with more comfort. Thus, a shaped cushion had been accurately designed (Virtual Prototype) and realized (Physical Prototype) aiming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In ergonomics-related research, the relationship between the contact area of body-touching parts and subjective comfort ratings is frequently discussed, particularly in the context of products such as seat cushions ( 26 , 27 ), exoskeletons ( 28 ), and pillows ( 29 ). Goonetilleke ( 30 ) posited that within the maximum pressure tolerance range, the contact area of a region correlates positively with perceived comfort.…”
Section: Footwear Comfort Plantar Pressure and Contact Areamentioning
confidence: 99%
“…In ergonomics-related research, the relationship between the contact area of body-touching parts and subjective comfort ratings is frequently discussed, particularly in the context of products such as seat cushions ( 26 , 27 ), exoskeletons ( 28 ), and pillows ( 29 ). Goonetilleke ( 30 ) posited that within the maximum pressure tolerance range, the contact area of a region correlates positively with perceived comfort.…”
Section: Footwear Comfort Plantar Pressure and Contact Areamentioning
confidence: 99%
“…For high-speed trains, the main task of mass travel, to meet the majority of people riding comfort for the purpose, it is difficult to do personalized design. Fiorillo et al [ 20 ] point out that seat-pan design is crucial and could be mainly influenced by two factors: pressure distribution and seat contour. de Mare et al [ 7 ] found that contoured seating bases can provide increased comfort and improved pressure distribution over flat seating bases.…”
Section: Introductionmentioning
confidence: 99%